Red Flags Associated With Knowledge Of Speech And Language Disorders Among Special Educators - Syed Tariq Shah; Nazia Mumtaz; Ghulam Saqulain (Journal of Rawalpindi Medical College)
Objective: To explore the knowledge about speech and language disorders among special educators of Army schools in Pakistan in association with qualification and experience.